METHOD OF THE USE OF ELECTRONIC INFORMATION AND COMMUNICATION MODULES IN THE SCHOOL GEOGRAPHICAL EDUCATION FOR SUSTAINABLE DEVELOPMENT - N. Vinokurova (Вестник Мининского университета, 2017)
The article considers and settle questions of method of the use of information and communication modules in the school geographical education, aimed at the development of information and communicative competence of students by means of geographical education for sustainable development.